Narrativas sobre a dinâmica prazer-sofrimento numa instituição bancária no Brasil - Moreira, Renata Pavão (2019)
The present study approaches the dynamics of pleasure and suffering at work through the lens of the psychodynamics of work, seeking the reports of workers of a banking institution, regarding the experience of pleasure and suffering at work. The objective of this research is to analyze the dynamics of pleasure-suffering at work as of the narratives of workers, seeking to understand the relation of this dynamic with the organization of banking work. For this matter, the study contextualizes the banking sector in relation to the changes in the work organization; addresses the dynamic pleasure-suffering at work and its relationship with the organization of work and discusses the results with the researched literature. The data were obtained by means of a narrative interview and subsequently submitted to thematic analysis when there have been identified the following core of analysis: (a) feeling and attitude at work; b) pleasure and satisfaction at work; c) suffering at work; d) dynamics of pleasure and suffering at work; e) mechanisms of defense of workers; f) balance between personal and professional life; g) organization of work; h) competitiveness and cooperation in the banking sector. At the end of the analysis, it was concluded that the participants enjoy their work in the company, but present situations of suffering related to some factors in the organization of work and interpersonal relationships. It should be emphasized that the same factor can be a generator of pleasure or suffering, in a dynamic process, depending on the moment, the context and the subjectivity of the worker.